Pentingnya Penerapan Cyber Notary Sebagai Upaya Terciptanya Keamanan Praktik Bisnis Di Indonesia - Marlin, Simon Reinaldo; Putra, Mohamad Fajri Mekka (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2022)
Doing Business, issued by the World Bank, emphasizes that it plays an important role in determining how easy it is to establish business indicators in Indonesia. The role of the Notary in the completion of a project. It's easy to test an index that combines speed and cost factors to determine how fast a business can grow. As a result, the faster and more precise the steps for creating a certificate, the easier it will be to determine your business indicators. The purpose of this research is to find out how dangerous the regulation of cybernotarius publicus under the Notary Position Law (UUJN) is to find out how easy business indicators are in Indonesia. This study uses normative legal methods. The findings of this study indicate that the Cyber Notary Agreement which regulates business transactions has been effective.